Genetic interrelationships of North American populations of giant liver fluke Fascioloides magna - Bazsalovicsová, Eva; Králová-Hromadová, Ivica; Štefka, Jan; Minárik, Gabriel; Bokorová, Silvia; Pybus, Margo (Parasites & vectors, 2015)
BACKGROUND: Population structure and genetic interrelationships of giant liver fluke Fascioloides magna from all enzootic North American regions were revealed in close relation with geographical distribution of its obligate definitive cervid hosts for the first time. METHODS: Variable fragments of the mitochondrial cytochrome c oxidase subunit I (cox1; 384 bp) and nicotinamide dehydrogenase subunit I (nad1; 405 bp) were applied as a tool. The concatenated data set of both cox1 and nad1 sequences (789 bp) contained 222 sequences that resulted in 50 haplotypes. Genetic data were analysed using Bayesian Inference (BI), Maximum Likelihood (ML) and Analysis of Molecular Variance (AMOVA). RESULTS: Phylogenetic analysis revealed two major clades of F. magna, which separated the parasite into western and eastern populations. Western populations included samples from Rocky Mountain trench (Alberta) and northern Pacific coast (British Columbia and Oregon), whereas, the eastern populations were represented by individuals from the Great Lakes region (Minnesota), Gulf coast, lower Mississippi, and southern Atlantic seaboard region (Mississippi, Louisiana, South Carolina, Georgia, Florida) and northern Quebec and Labrador. Haplotype network and results of AMOVA analysis confirmed explicit genetic separation of western and eastern populations of the parasite that suggests long term historical isolation of F. magna populations. CONCLUSION: The genetic makeup of the parasite's populations correlates with data on historical distribution of its hosts. Based on the mitochondrial data there are no signs of host specificity of F. magna adults towards any definitive host species; the detected haplotypes of giant liver fluke are shared amongst several host species in adjacent populations.
Keywords: Animals; Fascioliasis; Helminth Proteins; Electron Transport Complex IV; Ruminants; Molecular Sequence Data; respirační komplex IV; Deer; provincie Québec; Genetic Variation; Phylogeny; molekulární sekvence - údaje; Spojené státy americké; fasciolóza; Quebec; přežvýkavci; United States; proteiny červů; Fasciola hepatica; zvířata; fylogeneze; genetická variace; vysoká zvěř